Konsep Pendidikan Islam Sebagai Upaya Terapi Rehabilitas Pasien Narkoba - Wahyuningsih Wahyuningsih; Manshuruddin Manshuruddin (Departement of Mathematics Education, 2024)
This research is motivated by the concept of Islamic education as a therapeutic effort for the rehabilitation of drug patients. This research is a qualitative research. This type of research is a literature study or library research, which means a study carried out to solve a problem which basically relies on a critical and in-depth study of relevant library materials. a technique by collecting data through written remains, such as archives, including books about theories, opinions, postulates or laws, etc. related to research problems. The results of this research show that the concept of Islamic education as a therapeutic effort for the rehabilitation of drug patients includes prayer, fasting and remembrance. Prayer directly revives the spirituality of drug addicts, and one of the essences of prayer is to increase faith in submission and surrender to the giver of life. Praying directly will guide us to be better, the burden will be light, difficulties will be easy to face and problems will be resolved. Prayer is the material most emphasized by therapists for drug victims so that anyone who wants to get rid of problems can ask Allah for help with patience and prayer. Fasting is one of the therapeutic methods that can be applied to rehabilitation patients. There are five secrets of fasting that can be enjoyed, namely: a) Strengthening the soul b) Educating the will to be kind c) Making the body healthy d) Recognizing pleasure, and e) Remembering and feeling the suffering of others . Dhikr is an effort to get closer to Allah through the heart. It is hoped that the patient can feel directly the presence of Allah SWT and provide a spiritual experience that makes his heart moved and has a serious intention to repent and recover from drugs and become a person who is always close to Allah SWT. So the concept of Islamic education as a therapeutic effort for the rehabilitation of drug patients, including prayer, fasting and dhikr, is very effectively applied to drug rehabilitation patients.